Cadazolid for the treatment of Clostridium difficile. (3rd April 2017) - Endres, Bradley T.; Bassères, Eugénie; Alam, M. Jahangir; Garey, Kevin W.
ABSTRACT: Introduction : Antibiotic development goals for CDI include potent antimicrobial effect against C. difficile, limited killing of host microbiota, potential effect on spores, and ability to interfere with toxin production. Cadazolid, a novel, non-absorbable hybrid antibiotic has many of these criteria. In phase I and II clinical trials, cadazolid was shown to be safe, well tolerated, and efficacious positioning itself as a potential future viable therapeutic option for CDI. Areas covered : This review provides an in-depth evaluation of the chemistry, microbiology, pharmacodynamics, pharmacokinetics, and clinical trial results for cadazolid. Clinical therapeutic outcomes are compared between cadazolid, fidaxomicin, and surotomycin. Expert opinion : Preclinical and early clinical studies demonstrated that cadazolid has unique properties that will likely be valuable to treat CDI and reduce recurrent infection. With compelling phase II clinical results, results from the ongoing phase III trial will better define the role of cadazolid for treating CDI in the future.